Are Behavioral Effects of Early Experience Mediated by Oxytocin? - Bales, Karen L.; Boone, Ericka; Epperson, Pamela; Hoffman, Gloria; Carter, C. S. (Frontiers in Psychiatry, 2011)
Early experiences can alter adaptive emotional responses necessary for social behavior as well as physiological reactivity in the face of challenge. In the highly social prairie vole (Microtus ochrogaster), manipulations in early life or hormonal treatments specifically targeted at the neuropeptides oxytocin (OT) and arginine vasopressin (AVP), have long-lasting, often sexually-dimorphic, consequences for social behavior. Here we examine the hypothesis that behavioral changes associated with differential early experience, in this case handling the family during the first week of life, may be mediated by changes in OT or AVP or their brain receptors. Four early treatment groups were used, differing only in the amount of manipulation received during the first week of life. MAN1 animals were handled once on post-natal day 1; MAN1 treatment produces a pattern of behavior usually considered typical of this species, against which other groups were compared. MAN 1-7 animals were handled once a day for post-natal days 1-7, MAN 7 animals were handled once on post-natal day 7, and MAN0 animals received no handling during the first week of life. When tested following weaning, males in groups that had received manipulation during the first few days of life (MAN1 and MAN1-7) displayed higher alloparenting than other groups. Neuroendocrine measures, including OT receptor binding and OT and AVP immunoreactivity, varied by early treatment. In brain areas including the nucleus accumbens, bed nucleus of stria terminalis and lateral septum, MAN0 females showed increased OT receptor binding. MAN1 animals also displayed higher numbers of immunoreactive OT cell bodies in the supraoptic nucleus. Taken together these findings support the broader hypothesis that experiences in the first few days of life, mediated in part by sexually-dimorphic changes in neuropeptides, especially in the receptor for OT, may have adaptive consequences for sociality and emotion regulation.